2005
DOI: 10.1111/j.1742-6723.2005.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient delay and use of ambulance by patients with chest pain

Abstract: Education programmes should continue to emphasize that chest pain is a potential medical emergency and an ambulance should be called. GPs should consider developing an action plan to manage patients presenting with chest pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 13 publications
(15 reference statements)
2
25
1
Order By: Relevance
“…Despite numerous studies on the topic of patient-caused delays, 13,24,25 only one small study has specifically examined patients who have chest pain in association with acute myocardial infarction. 34 The predictors of patient-caused delay in our study were similar to those reported in previous studies of patients with acute myocardial infarction, who may or may not have had chest pain. 12,24,26,35 In other studies, older patients were more likely to present late, 12,13,24,25,35 but this was thought to be due in part to atypical symptoms, which are common in elderly people.…”
Section: Discussionsupporting
confidence: 79%
“…Despite numerous studies on the topic of patient-caused delays, 13,24,25 only one small study has specifically examined patients who have chest pain in association with acute myocardial infarction. 34 The predictors of patient-caused delay in our study were similar to those reported in previous studies of patients with acute myocardial infarction, who may or may not have had chest pain. 12,24,26,35 In other studies, older patients were more likely to present late, 12,13,24,25,35 but this was thought to be due in part to atypical symptoms, which are common in elderly people.…”
Section: Discussionsupporting
confidence: 79%
“…Almost less than one-third of the patients preferred ambulance for transportation and this rate was lower than the reported rates with previous studies from European countries and Australia but similar to the rates of China (4,(6)(7)(8). Instead of using ambulance most of our patients carried out the transportation to hospital in unsafe and inappropriate conditions for ACS.…”
Section: Discussioncontrasting
confidence: 52%
“…A questionnaire, which was formed by the investigators of the study according to the previous studies, was used (3,4,6,7). The questionnaire was prepared in order to assess patients' demographic, social and clinical characteristics, characteristic and severity of chest pain, presence of accompanying symptoms, the time between the onset of symptoms and arrival to the hospital and mode of transport to the hospital.…”
Section: Data Collectionmentioning
confidence: 99%
“…In Europe and australia, the figures often reach >50%, [40][41][42][43] whereas in the United States, the figures are often around 50% or lower. 35,44,45 More than two-third of the patients with StEMI in Beijing presented to the hospital by self-transport.…”
Section: Early Accessmentioning
confidence: 99%